2009
DOI: 10.1038/hr.2009.151
|View full text |Cite
|
Sign up to set email alerts
|

Association of PLA2G7 polymorphisms with carotid atherosclerosis in hypertensive Japanese

Abstract: Although the plasma platelet-activating factor-acetylhydrolase (pPAF-AH) gene (PLA2G7) polymorphisms are reportedly associated with atherosclerotic diseases, their effects in hypertensive patients have not been well examined. Thus, we genotyped V279F, a loss-of-function mutation commonly seen in the Japanese, and I198T and A379V commonly seen in Caucasians, and investigated the (1) ethnic differences in the frequencies and (2) association of these variants with prevalence of carotid plaque in 733 treated hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Including plasma Lp-PLA 2 mass or activity in the model did not attenuate the association between PLA2G7 SNPs and CAC. These findings support recent associations of variation in PLA2G7 with CHD (2931). …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Including plasma Lp-PLA 2 mass or activity in the model did not attenuate the association between PLA2G7 SNPs and CAC. These findings support recent associations of variation in PLA2G7 with CHD (2931). …”
Section: Resultssupporting
confidence: 90%
“…However in a meta-analysis of over 13,000 Asians, a common non-synonymous PLA2G7 SNP showed evidence of association with CHD (30). Additional non-synonymous SNPs have been associated with carotid plaque in Japanese (31) and recently a loss-of-function variant in PLA2G7 was shown to protect against CHD in Koreans (29). Due to the absence in Caucasian samples of the functional PLA2G7 SNP found in Asians (rs76863441 or V279F), we were not able to evaluate the effect of this functional variant in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM1 [340], ACSL1 [341], TLR4 [342], ABCA1 [343], TLR5 [344], CYP2D6 [345], JAK2 [346], NOTCH2 [347], DDX3X [348], NCOA4 [349], EGR1 [350], IQGAP2 [351], GCLC (glutamate-cysteine ligase catalytic subunit) [352], VEGFA (vascular endothelial growth factor A) [353], ITGB1 [354], LDLR (low density lipoprotein receptor) [355], TLR6 [316], SIRT1 [356], FGL2 [357], TET2 [358], PHF2 [328], VEGFB (vascular endothelial growth factor B) [359], SELENOM (selenoprotein M) [360], TRPM4 [361], OLFM2 [362] and ATAD3A [363] are thought to be involved in non-alcoholic fatty liver disease. Altered expression of ATOH8 [364], STAT1 [365], ARG1 [366], TLR4 [367], VNN1 [368], ABCA1 [369], IFIH1 [370], PTGS2 [371], F2RL1 [289], CYP2D6 [372], PDK4 [373], RNF213 [374], JAK2 [375], NOTCH2 [376], PDGFC (platelet derived growth factor C) [377], TLR2 [378], CYP1B1 [379], IL1RN [380], GCH1 [381], EGR1 [382], HIF1A [383], PLA2G7 [384], CCR2 [385], GAB1 [386], VEGFA (vascular endothelial growth factor A) [387], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [388], OXR1 [389], IRF9 [390], FMR1 [391], LDLR (low density lipoprotein receptor) [392], SIRT1 [393], NOD2 [394], ATP13A3 [395], VCAN (versican) [396], FGL2 [397], TET2 [398], KDM6A [399], KLHL2 [400], CAVIN1 [401], TNFRSF4 [402], PF4 [403], VEGFB (vascular endothelial growth factor B) [330], CCR7 [404], PRDX2 [405], HSPB1 [406], TCF4 […”
Section: Discussionmentioning
confidence: 99%
“…We used NetworkAnalyst database (https://www.networkanalyst.ca/) [45] database to find TFs regulating hub genes, IQGAP2 [351], GCLC (glutamate-cysteine ligase catalytic subunit) [352], VEGFA (vascular endothelial growth factor A) [353], ITGB1 [354], LDLR (low density lipoprotein receptor) [355], TLR6 [316], SIRT1 [356], FGL2 [357], TET2 [358], PHF2 [328], VEGFB (vascular endothelial growth factor B) [359], SELENOM (selenoprotein M) [360], TRPM4 [361], OLFM2 [362] and ATAD3A [363] are thought to be involved in non-alcoholic fatty liver disease. Altered expression of ATOH8 [364], STAT1 [365], ARG1 [366], TLR4 [367], VNN1 [368], ABCA1 [369], IFIH1 [370], PTGS2 [371], F2RL1 [289], CYP2D6 [372], PDK4 [373], RNF213 [374], JAK2 [375], NOTCH2 [376], PDGFC (platelet derived growth factor C) [377], TLR2 [378], CYP1B1 [379], IL1RN [380], GCH1 [381], EGR1 [382], HIF1A [383], PLA2G7 [384], CCR2 [385], GAB1 [386], VEGFA (vascular endothelial growth factor A) [387], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) …”
Section: Construction Of the Tf-hub Gene Regulatory Networkmentioning
confidence: 99%
“…Furthermore, Zheng et al demonstrated that the T198 allele was strongly associated with the risk of CHD with BSS (OR = 1.93, 95% CI: 1.21‐3.06) but not associated with the risk of CHD without BSS (OR = 1.47, 95% CI: 0.89‐2.44). Such a limited association was also observed in three studies included in Stafforini's review . Interestingly, two additional unrelated studies revealed quite different effects of the T198 allele on cardiovascular disease (CVD).…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 99%